FORMULATION AND CHARACTERIZATION OF MUCOADHESIVE BUCCAL TABLETS OF METOPROLOL SUCCINATE BY USING XANTHUM GUM - Kalyani, V.; Kishore, V. Sai; Padmini, G.; Nagasudha, R. K.V.; Kumar, M. Kalyan (Asian Journal of Pharmaceutical Research and Development, 2014)
In the present work, the mucoadhesive tablets of Metoprolol succinate were prepared by using xanthum gum as a binder. The four tablet formulation were prepared by using drug xanthum gum ratios of 1:0.5, 1:0.75, 1:1, 1:1.25 by direct compression technique. Tablets were subjected for evaluation of uniformity of weight, hardness, friability, drug content uniformity, Swelling studies, Surface pH study, Ex-vivo mucoadhesion time, Ex-vivo Bio adhesive strength and In vitro drug release study. Drug polymer interactions were evaluated by Fourier Transform Infrared Spectroscopy. All the formulations hardness, weight variation, friability and drug content values were found to be within pharmacopoeia limits. As the amount of polymer in the tablets increases, the drug release rate decreases, whereas swelling index and mucoadhesive strength increases. Based on the results F4was found to be optimized formulation. The in-vitro drug release of all formulations exhibits complete release of Metoprolol succinate with zero order release kinetics and followed by Higuchi mechanism. From the study it can be conclude that the Aegle marmelos gum used as a binding agent in mucoadhesive buccal tablet.